RELIGIOUS DOGMA IN SEBASTIÃN LELIOâ€™S THE WONDER (2022) - Anisa Hanifah; Mahi M. Hkikmat; Nurholis Nurholis (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
Religious issues that are no longer relevant to modern living are represented in The Wonder (2022) film by SebastiÃ¡n Lelio. This research aims to unravel the Religious Dogma in the film by focusing on examining the religious situation of Irish society in the nineteenth century. Tracing the religious life of the Irish community in the nineteenth century, where the majority adhered to Roman Catholicism, this research uses the sociology of literature method. In more detail, this research applies Max Weber's theory of the sociology of religion approach. The Wonder film entirely is the research data, but specifically, the writer takes the socio-religious context, screenshots from several scenes, and film dialogues as the secondary data. So it can be said that data collection in this research used documentation and literature study techniques. Analysis of the sociology of religion in The Wonder (2022) film by SebastiÃ¡n Lelio is still rare to find, so this research is essential so that it can add to criticism resources of the sociology of literature. Aside from that, the results of this research are that the modernization and logicalization of religion can occur along with times of development and the relevance of public interest.Â